The mummy trilogy [videorecording (Blu-Ray)] : the mummy ; the mummy returns ; The mummy : tomb of the Dragon Emperor - Sommers, Stephen; Gough, Alfred, 1967-; Millar, Miles; Fraser, Brendan, 1968-; Weisz, Rachel, 1970-; Hannah, John, 1962-; Vosloo, Arnold; Hyde, Jonathan, 1948-; O'Connor, Kevin J., 1964-; Fehr, Oded, 1970-; Velasquez, Patricia; Johnson, Dwayne, 1972-; et al. (Universal Pictures Home Entertainment, 2017)
"Embark on the ultimate action adventure that spans continents and centuries in the spectacular Mummy trilogy ... Follow the exhilarating journeys and exploits of daring explorer Rick O'Connell ... and his family as they combat the evil undead from the dusty tombs of Egypt to the hidden catacombs of China ..."--Container